Multi-Scale Porosity and Pore Structure Assessment of Shale - Yuan, Yujie (Curtin University, 2020)
A study of shale gas is conducted to investigate the influencing factors of the fundamental pore structure interpretations in shale gas reservoirs. The results reveal discrepancies between multi-scale techniques that are influenced by clay mineral content and organic matter. In this study, novel methods and calculation models are introduced for quantitative determination of nanopore structure parameters in shales. This study provides implications for shale formation evaluation in downhole practice.